A Factor Analysis of the Suicide Cognitions Scale in Veterans with Military Sexual Trauma-Related Posttraumatic Stress Disorder. Issue 3 (27th May 2021) - Wiblin, Jessica; Holder, Nicholas; Holliday, Ryan; Jeon-Slaughter, Haekyung; LePage, James; Surís, Alina
ABSTRACT: The Suicide Cognitions Scale (SCS) assesses suicide-specific cognitions which may drive suicide risk. Nonetheless, prior work has been mixed regarding optimal factor structure. Additionally, this measure has not been validated for use with veterans with military sexual trauma-related posttraumatic stress disorder (MST-related PTSD), a population that is at elevated risk for suicidal self-directed violence (SDV). This study sought to determine the optimal factor structure of the SCS for use with veterans with MST-related PTSD as well as its psychometric properties. An exploratory factor analysis revealed a four-factor structure, including unlovability, unbearability, unsolvability, and negative urgency. The SCS also demonstrated excellent internal consistency and good convergent validity. This study identified a novel factor, negative urgency, which may explain some of the predictive power of the SCS found in previous research. This paper provides initial support for a four-factor structure of the SCS among those with MST-related PTSD. Additional work remains necessary in evaluating the SCS as a tool for detecting risk for future suicidal SDV among veterans with MST-related PTSD.